Premature aging syndromes: From patients to mechanism. Issue 2 (November 2019) - Foo, Mattheus Xing Rong; Ong, Peh Fern; Dreesen, Oliver
Highlights: Laminopathies are diseases caused by mutations in components of the nuclear lamina. Progeria is an accelerated aging syndrome caused by a mutation in lamin A. Mutant lamin A triggers DNA damage, loss of heterochromatin and premature senescence. Cell- and mouse-based model systems provided mechanistic insights how mutant lamin A perturbs cell and organismal function. Experimental strategies for intervention are discussed. Abstract: Aging is an inevitable consequence of human life resulting in a gradual deterioration of cell, tissue and organismal function and an increased risk to develop chronic ailments. Premature aging syndromes, also known as progeroid syndromes, recapitulate many clinical features of normal aging and offer a unique opportunity to elucidate fundamental mechanisms that contribute to human aging. Progeroid syndromes can be broadly classified into those caused by perturbations of the nuclear lamina, a meshwork of proteins located underneath the inner nuclear membrane (laminopathies); and a second group that is caused by mutations that directly impair DNA replication and repair. We will focus mainly on laminopathies caused by incorrect processing of lamin A, an intermediate filament protein that resides at the nuclear periphery. Hutchinson-Gilford Progeria (HGPS) is an accelerated aging syndrome caused by a mutation in lamin A and one of the best studied laminopathies. HGPS patients exhibit clinical characteristics of premature aging, including alopecia, aberrant pigmentation, loss of subcutaneous fat and die in their teens as a result of atherosclerosis and cardiovascular complications. Here we summarize how cell- and mouse-based disease models provided mechanistic insights into human aging and discuss experimental strategies under consideration for the treatment of these rare genetic disorders.